Modele biznesowe wytwórców energii w mikroinstalacjach a zmiany otoczenia prawnego w sektorze energetyki odnawialnej - Stopa, Monika; Soliński, Bartosz (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
The functioning of the energy industry is largely based on legal norms and energy policies, which set the direction and development of business opportunities. The everchanging energy law creates opportunities for manufacturers operating in the renewable energy sector to adapt quickly to new conditions. The article presents the influence of changes in the field of energy law – the Act on Renewable Energy Sources – on the need to change business models of companies (renewable energy producers) determining their strategy in the energy market. Due to numerous legal changes in Poland in recent years, entrepreneurs have been forced to update existing business models. This paper analyzes the impact of legal aspects on renewable energy business models by presenting their variants in the light of the changing energy law, the scale needed to introduce model changes and strategies for further effective functioning on the energy market, and above all adaptation to new regulatory requirements.
Business models of micro-installation energy producers and changes in the legal conditions in the renewable energy sector
Keywords: business model; renewable energy; prosumer; renewable energy law; microinstallation